An immunologically relevant rodent model demonstrates safety of therapy using a tumour‐specific IgE. Issue 12 (8th October 2018) - Josephs, D. H.; Nakamura, M.; Bax, H. J.; Dodev, T. S.; Muirhead, G.; Saul, L.; Karagiannis, P.; Ilieva, K. M.; Crescioli, S.; Gazinska, P.; Woodman, N.; Lombardelli, C.; et al.
Abstract: Background: Designing biologically informative models for assessing the safety of novel agents, especially for cancer immunotherapy, carries substantial challenges. The choice of an in vivo system for studies on IgE antibodies represents a major impediment to their clinical translation, especially with respect to class‐specific immunological functions and safety. Fcε receptor expression and structure are different in humans and mice, so that the murine system is not informative when studying human IgE biology. By contrast, FcεRI expression and cellular distribution in rats mirror that of humans. Methods: We are developing MOv18 IgE, a human chimeric antibody recognizing the tumour‐associated antigen folate receptor alpha. We created an immunologically congruent surrogate rat model likely to recapitulate human IgE‐FcεR interactions and engineered a surrogate rat IgE equivalent to MOv18. Employing this model, we examined in vivo safety and efficacy of antitumour IgE antibodies. Results: In immunocompetent rats, rodent IgE restricted growth of syngeneic tumours in the absence of clinical, histopathological or metabolic signs associated with obvious toxicity. No physiological or immunological evidence of a "cytokine storm" or allergic response was seen, even at 50 mg/kg weekly doses. IgE treatment was associated with elevated serum concentrations of TNFα, a mediator previously linked with IgE‐mediated antitumour and antiparasitic functions, alongside evidence of substantially elevated tumoural immune cell infiltration and immunological pathway activation in tumour‐bearing lungs. Conclusion: Our findings indicate safety of MOv18 IgE, in conjunction with efficacy and immune activation, supporting the translation of this therapeutic approach to the clinical arena. Abstract : To study IgE class‐specific functions and safety, we designed a surrogate rat tumour model and rat equivalent antibodies of a human/chimeric IgE therapeutic candidate recognising a tumour associated antigen. IgE restricted tumour growth, elevated intratumoural immune cell infiltration and enhanced immune pathway activation, without clinical, histopathological or metabolic toxicity signs, nor immunological evidence of allergic response or cytokine storm. This model may inform translation of anti‐tumour IgE antibodies to clinical study, and help to dissect IgE functions in AllergoOncology, allergic inflammation, allergen immunotherapy and anti‐parasitic responses.